Noncompetitive homogeneous immunodetection of small molecules based on beta-glucuronidase complementation. Issue 9 (10th April 2018) - Su, Jiulong; Dong, Jinhua; Kitaguchi, Tetsuya; Ohmuro-Matsuyama, Yuki; Ueda, Hiroshi
Abstract : Small molecules can be sensitively detected with a positive signal by just mixing and measuring the β-glucuronidase activity within 20 min. Abstract : In this study, a novel noncompetitive homogeneous immunoassay for antigen detection was developed. We utilized β-glucuronidase (GUS), a homotetrameric enzyme, the assembly of all of whose subunits is necessary to attain its activity. By using a mutant GUS (GUSm), wherein the dimerization of dimers, which is a rate-limiting step, can be effectively inhibited by a set of interface mutations, we attempted to create a biosensor for detecting various molecules. Usually, the affinity between the two variable region domains (VH and VL ) of an antibody, especially for a small molecule, is relatively low. However, in the presence of an antigen, the affinity increases so that they bind tighter to each other. A pair of fusion proteins, comprising the VH and VL regions of the antibody as the detector tethered to a GUSm subunit as the reporter, was constructed to detect antigen 4-hydroxy-3-nitrophenylacetyl (NP) and bone Gla protein (BGP) through GUS activity measurement. Colorimetric and fluorescence assays could detect NP, 5-iodo-NP, and BGP within 1 h without separation steps and with a higher signal/background ratio than conventional ELISA. The instantaneous response after simple mixing of the components makes this system convenient and high-throughput. The system could be effective for the analyses of various small molecules in environmental and clinical settings.